Approaches to Discourse, Poetics and Psychiatry : Papers from the 1985 Utrecht Summer School of Critical Theory - Zavala, Iris M.; Dijk, Teun A. van; Díaz-Diocaretz, Myriam (John Benjamins Pub. Co., 1988)
A collection of innovative essays representing the most recent developments in poetry as discourse, the discourse of power, and discourse of psychiatry and psychosis. The essays in this volume deal with questions of interpretation of poetry, psychoanalysis, and political theory. All are presented here as appropriate objects of discourse studies which go beyond conventional analysis.